Conjuctive & Disjunctive Form Conversion - Is My Sollution Correct?

clytaemnestra

New member
Joined
Mar 7, 2021
Messages
7
Hi, I've solved a task, but I'm not sure if it's correct or not, as I'm doing it for the first time, thus I'd like to ask someone, if I got it correct.

Task: convert the following formula to the conjuctive, disjunctive and full disjunctive form:
(ϕ ⇒ ψ) ⇒ (¬ϕ ⇒ ¬ψ)

I went through Wiki and some materials on the internet and the method to solve it seems to be the following:
  • get rid of implication - p -> q = ¬ p ∨ q
  • use de Morgan's laws to get rid of negations
Solution: I've done the following:
(ϕ ⇒ ψ) ⇒ (¬ϕ ⇒ ¬ψ)
¬ (¬ϕ ∨ ψ) ∨ (¬¬ϕ ∨ ¬ψ)
(ϕ ∧ ¬ ψ) ∨ (ϕ ∨ ¬ψ) // this is disjunctive form
(ϕ ∧ ¬ ψ) ∨ ¬ (ϕ ∨ ¬ψ) // here I'm not sure if I can negate only one side, in order to change OR to AND?
(ϕ ∧ ¬ ψ) ∨ (¬ϕ ∧ ψ) // this is full disjunctive form
(ϕ ∨ ¬ ψ) ∧ (¬ϕ ∨ ψ) // this is (full) conjuctive form

Is this correct? Thank you in advance!
 
to go from line 3 to line 4, keeping logical equivalence, double negate the second bracket
(ϕ ∧ ¬ ψ) ∨ ¬¬ (ϕ ∨ ¬ψ)
(ϕ ∧ ¬ ψ) ∨ ¬ (¬ϕ ∧ ψ) // (de Morgan)
(ϕ ∧ ¬ ψ) ∨ ( (ϕ ∧ ψ) ∨ (ϕ ∧ ¬ψ) ∨ (¬ϕ ∧ ¬ψ) ) // the negation of the bracket, being disjunction of the three other combinations of conjunctions of ϕ, ψ, ¬ϕ, ¬ψ
(ϕ ∧ ψ) ∨ (ϕ ∧ ¬ψ) ∨ (¬ϕ ∧ ¬ψ) //full DNF
¬ (¬ϕ ∧ ψ) // reversing the substitution of the bracket just performed in the step before last
(ϕ ∨ ¬ψ) // (de Morgan) full CNF, also DNF (not full)


You could have gone straight from your line 3 DNF to full DNF:
(ϕ ∧ ¬ ψ) ∨ (ϕ) ∨ (¬ψ) // DNF
(ϕ ∧ ¬ ψ) ∨ ((ϕ ∧ ψ) ∨ (ϕ ∧ ¬ ψ)) ∨ ((ϕ ∧ ¬ ψ) ∨ (¬ϕ ∧ ¬ ψ)) // e.g. introducing the missing letter by replacing (ϕ) with ((ϕ ∧ ψ) ∨ (ϕ ∧ ¬ ψ)) etc...
(ϕ ∧ ψ) ∨ (ϕ ∧ ¬ψ) ∨ (¬ϕ ∧ ¬ψ) //full DNF
 
Hello, I have similar task to solve - to convert my formula into CNF, DNF and full DNF:
(φ ∧ ψ) ⇒ (¬φ⇒¬ψ)

My solution:

¬ ( φ ∧ ψ) ∨ (¬φ⇒¬ψ)
(¬ φ ∨ ¬ ψ) ∨ (¬φ⇒¬ψ)
(¬ φ ∨ ¬ ψ ) ∨ (ψ ⇒ φ)
(¬ φ ∨ ¬ ψ ) ∨ (¬ψ ∨ φ)
¬ φ ¬ ψ ¬ψ φ DNF, KNF
(¬ φ ∧ ψ) ∨ (¬φ ∧ ¬ψ) ∨ (¬ψ ∧ φ) ∨ (¬ψ ∧ ¬φ) ∨ (¬ φ ∧ ψ) ∨ (¬φ ∧ ¬ψ) ∨ (ψ ∧ φ) ∨ (ψ ∧ ¬φ) -> -> (¬ φ ∧ ψ) (¬φ ∧ ¬ψ) full DNF

Thanks for helping me out! :)
 
The fifth line reduces to
φ ∨ ¬ φ //(CNF and DNF)
which is a tautology. Therefore there is no full CNF and the full DNF is
( φ ∧ ψ) ∨ (φ ∧ ¬ψ) ∨ (¬φ ∧ ψ)∨ (¬φ ∧ ¬ψ)
 
The fifth line reduces to
φ ∨ ¬ φ //(CNF and DNF)
which is a tautology. Therefore there is no full CNF and the full DNF is
( φ ∧ ψ) ∨ (φ ∧ ¬ψ) ∨ (¬φ ∧ ψ)∨ (¬φ ∧ ¬ψ)

If I correctly understood, when I process from 4th to 5th line I do not have to write ¬ φ ∨ ¬ ψ ∨ ¬ψ ∨ φ. I simply get rid of both Psi's (since they are both negated) and only φ ∨ ¬ φ will remain? This is very helpful feedback, thank you Lex!
 
¬ ψ ∨ ¬ψ is clearly equivalent to ¬ ψ
so ¬ φ ∨ ¬ ψ ∨ ¬ψ ∨ φ is equivalent to φ ∨ ¬ ψ ∨ ¬ φ
but φ ∨ ¬ φ is already a tautology (it is always true) so any disjunction with it (e.g. ∨ ¬ ψ) is superfluous (it adds nothing) (it can't add any extra 'T' results to the truth table values, as they're all T already)
therefore the line is logically equivalent to simply φ ∨ ¬ φ
 
to go from line 3 to line 4, keeping logical equivalence, double negate the second bracket
(ϕ ∧ ¬ ψ) ∨ ¬¬ (ϕ ∨ ¬ψ)
(ϕ ∧ ¬ ψ) ∨ ¬ (¬ϕ ∧ ψ) // (de Morgan)
(ϕ ∧ ¬ ψ) ∨ ( (ϕ ∧ ψ) ∨ (ϕ ∧ ¬ψ) ∨ (¬ϕ ∧ ¬ψ) ) // the negation of the bracket, being disjunction of the three other combinations of conjunctions of ϕ, ψ, ¬ϕ, ¬ψ
(ϕ ∧ ψ) ∨ (ϕ ∧ ¬ψ) ∨ (¬ϕ ∧ ¬ψ) //full DNF
¬ (¬ϕ ∧ ψ) // reversing the substitution of the bracket just performed in the step before last
(ϕ ∨ ¬ψ) // (de Morgan) full CNF, also DNF (not full)


You could have gone straight from your line 3 DNF to full DNF:
(ϕ ∧ ¬ ψ) ∨ (ϕ) ∨ (¬ψ) // DNF
(ϕ ∧ ¬ ψ) ∨ ((ϕ ∧ ψ) ∨ (ϕ ∧ ¬ ψ)) ∨ ((ϕ ∧ ¬ ψ) ∨ (¬ϕ ∧ ¬ ψ)) // e.g. introducing the missing letter by replacing (ϕ) with ((ϕ ∧ ψ) ∨ (ϕ ∧ ¬ ψ)) etc...
(ϕ ∧ ψ) ∨ (ϕ ∧ ¬ψ) ∨ (¬ϕ ∧ ¬ψ) //full DNF

thank you very much for your help! :)
 
(ϕ ∧ ¬ ψ) ∨ ¬¬ (ϕ ∨ ¬ψ)
(ϕ ∧ ¬ ψ) ∨ ¬ (¬ϕ ∧ ψ) // (de Morgan)
(ϕ ∧ ¬ ψ) ∨ ( (ϕ ∧ ψ) ∨ (ϕ ∧ ¬ψ) ∨ (¬ϕ ∧ ¬ψ) ) // the negation of the bracket, being disjunction of the three other combinations of conjunctions of ϕ, ψ, ¬ϕ, ¬ψ
(ϕ ∧ ψ) ∨ (ϕ ∧ ¬ψ) ∨ (¬ϕ ∧ ¬ψ) //full DNF
¬ (¬ϕ ∧ ψ) // reversing the substitution of the bracket just performed in the step before last
(ϕ ∨ ¬ψ) // (de Morgan) full CNF, also DNF (not full)

I'd like to ask about the negation of the bracket, being disjunction of the three other combinations of conjunctions of ϕ, ψ, ¬ϕ, ¬ψ
I'm not sure I understand it completely. Which law or rule is it? How do I know how to combine these elements?
 
I'll write out something later this evening. In the meantime if you are in a hurry the same issue (with three 'letters') occurred in the above thread. (It may not help)!
 
I'd like to ask about the negation of the bracket, being disjunction of the three other combinations of conjunctions of ϕ, ψ, ¬ϕ, ¬ψ
I'm not sure I understand it completely. Which law or rule is it? How do I know how to combine these elements?
@clytaemnestra
I hope this makes it a bit clearer. (Maybe!) See attached
 

Attachments

  • negation.pdf
    239.6 KB · Views: 2
Top